Alloimmunization in Transfusion Dependent Thalassaemic Patients. - Ahmed, Saad H.; Al-Niami, Mayada S.; AL-Shammari, Haider H. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Life-long red blood cells (RBCs) transfusion remains the main treatment for severe cases of thalassaemia. The development of anti-RBC antibodies (alloantibodies and for autoantibodies) can significantly complicate transfusion therapy. Some alloantibodies are hemolytic and may cause, though not invariably, hemolytic transfusion reactions and limit the availability of further safe transfusion. Erythrocyte autoantibodies appear less frequently in blood cross match. Patients and methods: This is a descriptive study ducted at Al-Karama Thalassaemia Center in Baghdad .The sampling was done from September 2005 to April 2006 and all patients were diagnosed as Thalassaemia Major according to the hemoglobin electrophoresis results were included in the study (60 patients). Antibodies identification was carried out on serum employing commercial two cell panel, using standardized blood bank methods. If the patients were found to have irregular red cell alloantibodies, then the antibodies identification was performed by indirect coombs test using 18 panel cells. Results: Sixty thalassaemic patients were included in the study, 35 patients were males and 25 females. The age of patients ranged from 18 months to 33 years (median 25.2 7). Irregular red cell antibodies were found in 9 patients (15%). Mean age of patients who developed red cell antibodies was 25.2±7.0 years. Two patients developed autoantibodies (3.3%) and seven patients developed alloantibodies (11.7%).Six patients developed single antibodies (10%) while 3 patients developed multiple antibodies (5.0%). Total anti-k was found in 4 patients (6.7%), two patients had anti-k 1 and two patients had anti-k2. The higher rate of alloimmunization was in the rhesus Rh system, which was detected in (8.3%) 5 patients (one patient developed anti-D, one patient developed anti-c and 3 patients developed total anti-e). while total anti-M presented in 3 patients(5.09%)while one patient developed anti-Lea (1.7%). Conclusion: We concluded that there is a relatively high rate of alloimmunization in our set of patients when compared to data from Iraq geographic region. However, more data required from various other large centers in Iraq. It is recommended that red cell alloimmunization should not be overlooked in patients with B- thalassaemia major receiving regular blood transfusion. Those patients with Thalassaemia Major repeatedly suffer from hemolytic transfusion reaction or not being able to maintain hemoglobin at desired level in spite of regular transfusion due to the presence of irregular alloantibodies in their circulation. Proper blood cross matching, regular screening, detection & identification of the red blood cell alloantibodies would add towards the better management of these patients & reduce the chance of development of these irregular antibodies & other possible additional alloantibodies.